Dendritic cell-derived hepcidin sequesters iron from the microbiota to promote mucosal healing - Cloonan, Suzanne (My University, 2020)
Bleeding and altered iron distribution occur in multiple gastrointestinal diseases, but theimportance and regulation of these changes remain unclear. We found that hepcidin, themaster regulator of systemic iron homeostasis, is required for tissue repair in the mouseintestine after experimental damage. This effect was independent of hepatocyte-derivedhepcidin or systemic iron levels. Rather, we identified conventional dendritic cells (cDCs) asa source of hepcidin that is induced by microbial stimulation in mice, prominent in theinflamed intestine of humans, and essential for tissue repair. cDC-derived hepcidin actedon ferroportin-expressing phagocytes to promote local iron sequestration, which regulated themicrobiota and consequently facilitated intestinal repair. Collectively, these results identify apathway whereby cDC-derived hepcidin promotes mucosal healing in the intestine throughmeans of nutritional immunity.
PUBLISHED
Keywords: mucosal healing; gastrointestinal diseases; systemic iron homeostasis; mucosal healing; gastrointestinal diseases; systemic iron homeostasis